Implementasi strategi pemasaran syariah dalam meningkatkan nasabah produk pembiayaan Perbankan Syariah - Laksana, Elwi Yuda; Rahayu, Yayuk Sri (Maliki Interdisciplinary Journal, 2024)
Marketing strategy is one of the activities that producers must carry out to develop a company, in sharia banking there is such a thing as sharia marketing strategy, sharia marketing strategy does not escape Islamic law, in this research it can be concluded that sharia marketing strategies are quite effective in being carried out by companies. but there are several obstacles faced by the company in this case the researcher will conduct research at the Panin Dubai Syariah Islamic Bank to review the phenomena that occur in sharia marketing strategies